The Recovery of Weight-Bearing Symmetry After Total Hip Arthroplasty Is Activity-Dependent - Alves, Sónia A.; Preuße, Marco; Hommel, Hagen; Duda, Georg N.; Agres, Alison N. (Frontiers in Bioengineering and Biotechnology, 2022)
This study aimed to characterize ipsilateral loading and return to weight-bearing symmetry (WBS) in patients undergoing total hip arthroplasty (THA) during activities of daily life (ADL) using instrumented insoles. A prospective study in 25 THA patients was performed, which included pre- and controlled postoperative follow-ups in a single rehabilitation center of an orthopedic department. Ipsilateral loading and WBS of ADLs were measured with insoles in THA patients and in a healthy control group of 25 participants. Measurements in the THA group were performed at 4 different visits: a week pre-THA, within a week post-THA, 3 to 6 weeks post-THA, and 6 to 12 weeks post-THA whereas the healthy control group was measured once. ADLs included standing comfortably, standing evenly, walking, and sit-to-stand-to-sit (StS) transitions. All ADLs were analyzed using discrete methods and walking included a time-scale analysis to provide temporal insights in the ipsilateral loading and WBS waveforms. THA patients only improved beyond their pre-surgery levels during standing comfortably (ipsilateral loading and WBS, p<0.05) and StS transitions (WBS, p<0.05). Nevertheless, patients improved upon their ipsilateral loading and WBS deficits, which were observed within a week post-surgery across all investigated ADLs. Ipsilateral loading and WBS of THA patients were comparable to healthy participants at 6 to 12 weeks post-THA, except for ipsilateral loading during walking (p<0.05) at the initial and terminal double-leg support period of the stance phase. Taken together, insole measurements allow for the quantification of ipsilateral loading and WBS deficits during ADL, identifying differences between pre-operative and post-operative periods, and differentiating THA patients from healthy participants. However, post-THA measurements that lack pre-surgery assessments may not be sensitive to identifying patient-specific improvements in ipsilateral loading and WBS. Moreover, StS transitions and earlier follow-up time points should be considered as an important clinical metric of biomechanical recovery after THA.